Uma abordagem diferente para o ensino da função exponencial no Ensino Médio - Angelucci, Michel (Universidade Federal de São Carlos, 2014)
The objective of this essay is to propose a different approach to teaching the exponential function in high school. This new approach aims to provide a meaningful learning related to the subject exponential function, since students and teachers sometimes have difficulty understanding this concept, especially when it comes to real exponents. The work was based on preparation of some activities based on the Theory of Didactical Situations and applied following the methodology of the Didactic Engineering. There were basically five activity sheets, three of them were printed and two of them were spreadsheets. The problems and exercises aimed to examine and extend the validity of the fundamental property of exponential functions, that is, f(m + n) = f(m):f (n) for the dominance of natural numbers, integer, rational, real, and for the last one, we only worked with spreadsheets, specifically in the activity sheet number 5, to afford students an understanding about how the calculator obtains the approximate result of 2 √2 for example. The spreadsheet was also used in the activity sheet number 4, which deals with rational exponents. On this one we present an algorithm for the approximate calculation of nth roots of any real number. The activity sheets have been developed in order to provide students with maximum autonomy so that they could resolve them, being interspersed with adjunct sheets in order to introduce the new concept and theory discussed in the following activity sheet. The activities were implemented at a state school in It´apolis, and the results in a final analysis showed that this approach supplied a significant learning compared to traditional teaching.
Keywords: Ensino de Matemática; Função exponencial; Engenharia Didática; Situações didáticas; Teaching of Mathematics; Exponential function; Didactic (or Teaching) Engineering; Didactic (or Teaching) situations; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ANALISE